Mechanisms for Empowering Teacher Innovation in the Development of Learning Practices: An Islamic Education Perspective - Didit Darmawan; Hasan Hasan; Ahmad Jamali (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to formulate a conceptual mechanism for empowering teacher innovation in the development of learning practices from the perspective of Islamic education. The study employs a qualitative approach with a literature review design to synthesize knowledge on teacher innovation, educational management, and Islamic educational thought. Relevant literature was systematically collected from trusted academic databases using keywords related to teacher innovation, human resource management in education, and Islamic education. Data were analyzed through content analysis to identify recurring themes and construct an integrative conceptual framework, while the validity of the findings was strengthened through source triangulation by comparing evidence from multiple independent references. The findings reveal that teacher innovation empowerment is developed through five interconnected mechanisms: (1) strengthening niyyah (spiritual intention) and professional commitment; (2) enhancing pedagogical competence and reflective learning practices; (3) fostering collaborative knowledge sharing based on the principles of shūrā and taʿāwun; (4) reinforcing institutional support through transformational leadership and an innovation-oriented school culture; and (5) implementing continuous evaluation guided by the principles of iḥsān and muḥāsabah. These mechanisms position teacher innovation as a holistic process that integrates spiritual values, ethical responsibility, professional competence, and organizational support in improving learning practices. The novelty of this study lies in the development of an Islamic education-based framework for teacher innovation empowerment that systematically integrates spiritual, pedagogical, social, managerial, and institutional dimensions into a comprehensive conceptual model, thereby offering a distinctive alternative to the predominantly secular paradigms of educational innovation.